Florida Studies. - Slate, Claudia (Cambridge Scholars Pub., 2007)
Florida was the first region of the United States to be discovered, explored, and, after a fashion, settled by Euroamericans. Its population in the early 21st century is approaching 17 million. Within years the number of people living in the state will surpass those living in New York, and the Sunshine State will become the most populous area east of the Mississippi. The first book in English about Florida was written by Jean Ribault. A French adventurer, Ribault established a colony of Hugue ...